BILINGUISMO E CONTATO LINGUÍSTICO NO JORNAL PRÁCIA NO MUNICÍPIO DE PRUDENTÓPOLIS-PR - RAMOS, ANDRIELI BASNIAK LOPES DOS SANTOS (2023)
This research proposes an analysis of the editorial content from the newspaper 'Праця' (Prácia), initially produced by Ukrainian immigrants and today by their descendants, in the Municipality of Prudentópolis-PR, with the purpose of understanding the relationships that result from bilingualism and contact language at the lexical level between the Ukrainian language and the Portuguese language. The newspaper began to be published in 1912, being today one of the oldest newspapers still in circulation, bringing in its pages diverse themes about uses, customs and representations of the Ukrainian community established in Prudentópolis, since the end of the 19th century. After observing the configuration of the newspaper, the column “Пише Юджо” was chosen, which in translation to Portuguese is entitled “Iujo Chelo writes”, written and edited by Fr. Tarcisio Zaluski. The time frame from 1994 to 2019 was defined, since the material already has almost three decades of publications, and therefore it was chosen to take as a starting point the first publication of the column, which occurred in the edition from June 16 to 30, 1994 and the editions of the same month of the years 1999, 2004, 2009, 2014 and 2019. Therefore, this research proposes to analyze the marks of linguistic contact that exist between the languages in use in the region and that are present in the column of Prácia selected. As a theoretical-methodological support, this research is based on Variationist Sociolinguistics, on studies of Bilingualism and Languages in Contact. At the end of this research, it was possible to conclude that the result resulting from the contact between the languages in use in the region led to significant changes in the Ukrainian language spoken in the municipality. Thus, with this research, we hope to have contributed to discussions about situations linguistically similar to those in Prudentópolis.